PENERAPAN E-COMMERCE PADA USAHA BATIK JAMBI PADA TOKO BATIK DUO SERANGKAI: Customers, Promotion, E-Commerce, Batik. - Sany, Ezrifal; Kurniawan, Yudiyanto (LP2M Universitas Nurdin Hamzah, 2023)
With today’s technological development, human activities are becoming more and more easy to do, as sales and sales activities have been broken down with what is called